Practices of Organizing Built Space in Videoconference-Mediated Interactions. Issue 4 (1st October 2016) - Hjulstad, Johan
ABSTRACT: This article investigates practices used to address recipients during videoconference-mediated classroom interaction. In the classroom setting studied, the aim is to teach sign language to students. The video-mediated environment (VME) represents a "fractured" environment that constrains the way in which gaze and pointing can be used. The article explores how signing teachers and students build composite utterances that employ and juxtapose various resources simultaneously for coordinated action, recruiting the signing space to inscribe meaning. The findings show that referential mapping allows actors to manage the fractured ecology of a multiparty VME. The management is demonstrated by one teacher who uses pointing in a new way for referential mapping in order to establish reliable addressing practices and next speaker selection. Consequently, the mapping practice becomes a solution for the "deictic" complexities of nonshared spaces. The article contributes to our understanding of interaction in VMEs. Data are in Norwegian Sign Language.